2016
DOI: 10.1088/1367-2630/18/6/063028
|View full text |Cite
|
Sign up to set email alerts
|

Seeking large thermoelectric effects in MgO-based tunnel junctions

Abstract: There is much controversy concerning thermoelectric effects in the MgO-based magnetic tunnel junctions (MTJs) as reported in some recent publications. To clarify the problem, we give calculations from atomic first-principles systemically. Large Seebeck coefficient (S) and up-limit of figure of merit (ZT) are predicted in double-and multi-barrier MTJs, with those in single-barrier MTJs being relatively small. By restraining the phonon thermal conductance through the introduction of one vacuum barrier or numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In the definition, since there is usually no periodicity along the z axis in MTJs, we use G/A, the conductance divided by the cross-sectional area of the MTJ, instead of the electrical conductivity, which is the analog of the resistance area product RA and used in Ref. [25]. The power factor of the Fe(7ML)/MgO(nML)/Fe(7ML)(001) MTJ (from n = 3 to n = 12) for the parallel magnetization configuration for the compressive and the extensive tetragonal distortions of the in-plane lattice parameter is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the definition, since there is usually no periodicity along the z axis in MTJs, we use G/A, the conductance divided by the cross-sectional area of the MTJ, instead of the electrical conductivity, which is the analog of the resistance area product RA and used in Ref. [25]. The power factor of the Fe(7ML)/MgO(nML)/Fe(7ML)(001) MTJ (from n = 3 to n = 12) for the parallel magnetization configuration for the compressive and the extensive tetragonal distortions of the in-plane lattice parameter is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the interfacial termination has been found to affect the Seebeck effect in MTJs [18,23,24]. Furthermore, Jia et al [25] have reported that the interface resonant tunneling significantly changes the energy dependence of the tunneling conductance. They have calculated the Seebeck coefficient of Fe/MgO/Fe(001) MTJs, which are known to exhibit interface resonant tunneling due to the large DOS of minority-spin states at the interface [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TMS in double-barriers [108,109] and the role of magnon transport in the TMS [110] have been discussed recently from the theoretical side. However, experiments following these ideas have not yet been conducted.…”
Section: Discussionmentioning
confidence: 99%